Molding foaming composition and foaming process
By using polyether polyols, amine catalysts, triblock copolymer-organic montmorillonite and other components in the molding foaming composition, combined with the low-temperature molding foaming process, the problems of low mold usage, long production cycle and serious heat waste in traditional thermal molding technology are solved, and the production cycle is shortened, thermal energy saving and material performance are improved.
Patent Information
- Application Number
- CN202510184280.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-04-29
AI Technical Summary
In traditional thermal molding technology, the mold usage rate is low, the production cycle is long, the heat consumption is large, the heat energy is wasteful, and the catalyst consumption is large.
A molded foam composition is adopted, including component A and component B, which consists of polyether polyol, polymer polyol, amine catalyst, silicone oil, triblock copolymer-organic montmorillonite and water, and component B is isocyanate. By molding and maturing at low temperatures, heat energy consumption is reduced, and the hydrogen bonding and topological network of foamed materials is constructed using triblock copolymer-organic montmorillonite to improve the strength and toughness of the materials.
The production cycle is shortened, the heat energy saving, the catalyst reduction, the material has a high rebound rate and high compression ratio, and good flame retardant performance is achieved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastics, in particular to a molding foaming composition and a foaming process. Background Art
[0002] The molded foam composition is generated by the reaction of polyurethane raw materials in a mold; the molded product can directly replicate the shape of the mold, is comfortable to use, and is more economical, reducing labor costs and waste of foam plastics; when the molded product is produced, all reaction components react in one step in the mold, and can be processed using high-pressure or low-pressure molding machinery; because the molds must be filled one by one, the production method is intermittent.
[0003] According to the reaction characteristics of raw materials, there are two main molding methods used in the polyurethane industry, namely hot-curing molding and cold-curing molding. The mold utilization rate in hot molding is relatively low, because its production cycle is long, and it needs to go through a 110-300℃ drying tunnel to accelerate curing, which wastes heat seriously, consumes too much energy, and requires more catalysts. Summary of the invention
[0004] The purpose of the present invention is to provide a molding foaming composition, which solves the problems of traditional thermal molding, such as low mold utilization rate, long production cycle, high heat consumption, serious waste of heat energy and high catalyst consumption.
[0005] Another object of the present invention is to provide a foaming process for a molding foam composition, which is used to prepare a cold-cured high-resilience molding foam composition.
[0006] The present invention is achieved through the following technical solutions:
[0007] A molding foaming composition comprises a component A and a component B. The component A comprises, by weight, 75-85 parts of polyether polyol, 15-30 parts of polymer polyol, 0.5-1.5 parts of diethanolamine, 1-3 parts of silicone oil, 0.1-0.5 parts of triethylenediamine, 0.2-0.8 parts of dimethylethanolamine, 0.1-1 parts of triblock copolymer-organic montmorillonite and 2-6 parts of water. The component B is isocyanate.
[0008] A foaming process for a molded foaming composition comprises the following steps:
[0009] S1. Stirring the A component at a speed of 50-100 r / min for 5 min; S2. Stirring the B component at a speed of 15-20 r / min for 2 min; S3. Mixing the A component and the B component, stirring at a speed of 15-20 r / min for 5 s, and then pouring into a mold for reaction to obtain the molding foaming composition.
[0010] The technical solution of the present invention has at least the following advantages and beneficial effects:
[0011] The method adopts high molecular weight (M=4500-6500, hydroxyl value 26-35mgK0H / g) and high activity (primary hydroxyl 60%-90%) polyether triol as the basic raw material, takes high efficiency amine catalyst and low activity organosilicon foam stabilizer as auxiliary agents, and performs molding, foaming and aging at low temperature (30-65°C); only a small amount of heat is required from the outside during the production process, which can save a lot of heat energy; the produced cold-aging high-resilience molding foaming composition has high resilience and high compression ratio; at the same time, qualified flame retardant performance can be obtained by adding a small amount of catalyst; at the same time, the production cycle is short, the foaming can be completed in a short time, a large number of molds can be saved, and a large amount of operating costs can be saved.
[0012] During the flow of polyurethane foam, viscosity increases gradually. In the initial stage of reaction, viscosity is relatively low, but with the strengthening of cross-linking reaction, especially when gel time is approaching, viscosity rises rapidly. According to Newton's viscosity law, viscosity increase causes the bubble velocity gradient to improve. When the bubble velocity gradient is large, any flow resistance may be involved in bubbles, and then form the cavity in the polyurethane foam, affecting material strength and toughness. Therefore, the present invention utilizes triblock copolymer-organic montmorillonite to construct hydrogen bond and topological network of foaming material, organic montmorillonite regulates nucleation, growth and stability of material pores, triblock copolymer and polyurethane molecular chain are mutually entangled to form physical entanglement points, so that the structure of pores is more stable, and hydrogen bond sacrificial unit is constructed at filler-polyurethane elastic matrix interface simultaneously, and extra strain energy is dissipated by the destruction of hydrogen bond sacrificial unit in strain process, thereby achieving the simultaneous improvement of strength and toughness of material, overcoming the problem that montmorillonite reduces material toughness under reinforcement.
[0013] The triblock copolymer and the montmorillonite crystal layer are interlaced with each other. During the coagulation process, the pyridine group in the polymer reacts with the hydrogen ions, so that the copolymer has a cationic side group. This side group can produce electrostatic adsorption with the negatively charged montmorillonite crystal layer, so that the movement of the macromolecular chain segment is restricted, which plays a good reinforcing role in the material. On the one hand, it can improve the compatibility and dispersibility of montmorillonite in the material; on the other hand, the polyethylene glycol on the surface of the organic montmorillonite will generate hydrogen bonds with the polyurethane molecular chain. Since the dissociation energy of the hydrogen bond generated between the polyurethane and the polyethylene glycol is less than the dissociation energy of the carbon-carbon covalent bond, these hydrogen bonds will first gradually dissociate during the stretching process, and a large amount of strain energy will be consumed during the dissociation process, thereby improving the toughness of the material; thirdly, the polyethylene glycol molecular chain and the polyurethane molecular chain are close to each other. During the placement or heat treatment process, the polyethylene glycol molecular chain will regenerate hydrogen bonds with the polyurethane molecular chain to achieve reversible recovery of the hydrogen bond, thereby improving the tensile strength and elongation at break of the material. DETAILED DESCRIPTION
[0014] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0015] On the one hand, the present invention provides a molding foaming composition, comprising component A and component B, wherein component A comprises, by weight, 75-85 parts of polyether polyol, 15-30 parts of polymer polyol, 0.5-1.5 parts of diethanolamine, 1-3 parts of silicone oil, 0.1-0.5 parts of triethylenediamine, 0.2-0.8 parts of dimethylethanolamine, 0.1-1 parts of triblock copolymer-organic montmorillonite and 2-6 parts of water, and component B is isocyanate.
[0016] The chemical reaction principle of the wood molding foaming composition of the present invention comprises:
[0017] 1) Polymerization reaction
[0018] Hydroxyl-containing polyols react with isocyanates to form urethanes through a stepwise polymerization reaction:
[0019] RN=C=O+R′-OH→R-NH-CO-OR′
[0020] 2) Foaming reaction
[0021] When isocyanate reacts with water, carbon dioxide is released and diurea is generated: an intermediate product with extremely poor thermal stability, carbamic acid, is first generated, which can naturally decompose to produce carbon dioxide and primary amines, and then the primary amines react with another isocyanate molecule to form diurea:
[0022] RN=C=O+HOH→[R-NH-COOH]
[0023] [R-NH-COOH] → R-NH2 + CO2↑
[0024] R-NH2+R-NCO↓→R-NH-CO-NH-R
[0025] 3) Cross-linking reaction
[0026] At higher temperatures, the active hydrogen in the carbamate can further react with another isocyanate molecule to form allophanate:
[0027] R-NH-COO-R′+RN(CO-NH-R)-COO-R′
[0028] Diurea further reacts with isocyanate to form biuret:
[0029] R-NH-CO-NH-R+R-NCO→R-NH-CO-NR-CO-NH-R
[0030] In the urea-forming reaction, the carbon dioxide-like reaction mixture is foamed and gradually expands, and finally a foam plastic having an open-cell structure is obtained.
[0031] Polyether polyols are polyether triols, which are used to produce high-resilience polyurethane foam plastics. They have excellent resilience and softness and are widely used in various fields, especially furniture, automobiles, footwear, packaging materials, etc.
[0032] The polymer polyol adopts high resilience polymer polyol H45 (or CHP-H45), which makes the polymerization reaction more rapid and efficient, is beneficial to improving the performance and stability of foam plastics, facilitates processing and molding, and improves the strength and durability of foam plastics. It is particularly suitable for the preparation of high resilience polyurethane foam plastics.
[0033] As a cross-linking agent, diethanolamine can promote polymerization reaction, thereby accelerating the foaming rate; it can also make the bubbles more stable by reducing bubble breakage and merging phenomena; at the same time, an appropriate amount of diethanolamine can control the bubble size and improve the foaming quality.
[0034] Dimethylethanolamine can significantly accelerate the condensation reaction of polyether polyols and diisocyanates (such as TDI), ensuring that the reaction quickly reaches the ideal state at a suitable temperature. It releases heat by reacting with TDI and generates isocyanate compounds and dimethylaminoethanol, which are then converted into CO2 and water vapor, driving the expansion of polyurethane foam and forming an ideal foam structure.
[0035] A-33 is a catalyst that can catalyze the gelation reaction of polyurethane foam and promote the curing process of the foam. A-33 can also improve the fluidity, uniformity and stability of the foam through catalysis, thereby improving the overall performance of the foam.
[0036] Dimethylethanolamine (DMAE or DMEA) is used as a catalyst in the foaming process. Dimethylethanolamine can significantly accelerate the condensation reaction of polyether polyols and diisocyanates (such as TDI), ensuring that the reaction quickly reaches the ideal state at a suitable temperature. At the same time, it releases heat through the reaction with TDI and generates isocyanate compounds and dimethylaminoethanol. These products are then converted into CO2 and water vapor, which promote the expansion of polyurethane foam and form an ideal foam structure.
[0037] The silicone oil is silicone oil 6080, which acts as a stabilizer in the foaming process, can reduce surface tension, and is beneficial to the uniformity of the foam. It can stabilize the pores, reduce gas diffusion, and make the foam more delicate and uniform. In the foaming process, silicone oil can quickly increase the viscosity of the material, which helps to slow down the rapid thinning of the pores and prevent the pores from being coarse and uneven or even collapsing. Appropriate viscosity is beneficial to the stability and formability of the foam. Silicone oil can increase the strength of the pore membrane wall and pore meridians, making the foam stronger and more durable; it helps to improve the compression resistance and service life of the foam; silicone oil can also reduce the mixing of impurities into the foam, avoid the collapse and voids caused by the reduction of local surface tension of the pores; it helps to maintain the integrity and aesthetics of the foam.
[0038] The triblock copolymer is composed of alternating poly-4-vinylpyridine (P4VP) segments and polystyrene (PS) segments, presenting a unique bifunctional molecular structure. The poly-4-vinylpyridine (P4VP) segment contains pyridine groups, has weak alkalinity and coordination ability, can form complexes with metal ions, hydrogen bond donor molecules or acidic molecules, and provides good hydrophilicity and chemical functionalization ability; the polystyrene (PS) segment is a rigid skeleton, which gives the material mechanical strength and structural stability, improves the thermal stability and chemical resistance of the overall material, the middle PS segment provides rigid support, and the P4VP segments on both sides provide chemical activity, so that it exhibits unique characteristics in nanoassembly and interface modification. The hydrophilicity of the P4VP segment and the hydrophobicity of the PS segment give the material good two-phase interface properties, which is convenient for self-assembly and phase separation. The pyridine group of the P4VP segment is chemically active and can combine with acids, metal ions or organic molecules to achieve a variety of functionalization transformations. The PS segment provides excellent thermal stability and wear resistance, enhancing the overall performance of the material. The triblock copolymer exhibits regular phase separation behavior in the field of self-assembly and can form lamellar, spherical or columnar microphase structures.
[0039] Polyurethane elastomers are composed of soft segments (oligomer polyols) and hard segments (isocyanates). The relative molecular mass of oligomer polyols is polydisperse, while polyisocyanates are often a mixture of multiple isomers. The presence of isomers will destroy the regularity of the hard segment, reducing the heat resistance of the elastomer. The use of triblock copolymers can increase the mass fraction of the hard segment, form more hard segment ordered structures and secondary crystal structures, reverse the two phases, and make the hard segment phase become a continuous phase. The soft segment is dispersed in the hard segment phase, thereby improving the tensile strength and heat resistance of the elastomer at high temperatures.
[0040] In the present invention, the triblock copolymer is poly-4-vinylpyridine-polystyrene-poly-4-vinylpyridine, and the organic montmorillonite is polyethylene glycol-modified montmorillonite.
[0041] In the present invention, the preparation method of the triblock copolymer-organic montmorillonite is as follows: a) dispersing the organic montmorillonite in water to obtain a suspension with a solid content of 20-25%; b) adding the suspension to the triblock copolymer latex, mixing uniformly, washing, and drying to obtain a mixed material; c) demulsifying the triblock copolymer latex with calcium chloride, drying to obtain a copolymer; d) mixing the copolymer and the mixed material at a mass ratio of 10:1. The mass of calcium chloride is 0.1%-1% of the triblock copolymer latex. The mass ratio of the triblock copolymer to the organic montmorillonite is 8:1.
[0042] In the present invention, the preparation method of the organic montmorillonite is as follows: dispersing sodium-montmorillonite in anhydrous ethanol at a mass ratio of 50:1, adding polyethylene glycol in an amount of 20% of the mass of the sodium-montmorillonite for reaction, and drying. The sodium-montmorillonite is sodium-nano-montmorillonite.
[0043] In the present invention, the mass ratio of component A to component B is 5:1.8-2.2.
[0044] In the present invention, the polyether polyol is a polyether triol with a molecular weight of 4500-6500, a hydroxyl value of 26-35KOH / g, and a primary hydroxyl group of 60%-90%; the polymer polyol is a high-resilience polymer polyol H45; and the triethylene diamine is a triethylene diamine solution with a mass fraction of 33%.
[0045] In the present invention, the isocyanate includes methyl diisocyanate and polymethylene polyphenyl polyisocyanate in a mass ratio of 1:1. TDI (toluene diisocyanate) and polymeric MDI (polymethylene polyphenyl polyisocyanate) are two important raw materials. TDI contains two isocyanate groups (-NCO), which have high reactivity. The foam plastic produced using it has good heat insulation, sound insulation and cushioning properties, and provides comfortable elasticity and support. Polymeric MDI is a mixture of polyisocyanates with different functionalities, with an average functionality of 2.5-2.8. It is mainly composed of diisocyanate (MDI), triisocyanate and a small amount of polyisocyanate; it mainly produces polyurethane rigid foam and semi-rigid foam.
[0046] In the present invention, the component A also includes 1-1.5 parts of a colorant by weight, and the colorant is black paste 6025. The color paste is mainly used for color matching, and the corresponding color can be selected according to production needs, and most people choose black.
[0047] On the other hand, the present invention provides a foaming process for a molded foaming composition, comprising the following steps: S1, stirring a component A at a speed of 50-100 r / min for 5 min; S2, stirring a component B at a speed of 15-20 r / min for 2 min; S3, mixing the component A and the component B, stirring at a speed of 15-20 r / min for 5 s, and then pouring the mixture into a mold for reaction to obtain the molded foaming composition.
[0048] Specifically, in step S3, the reaction temperature is 30-65°C.
[0049] Example 1
[0050] A foaming process for a molded foaming composition comprises the following steps:
[0051] Preparation of organic montmorillonite:
[0052] The sodium-nano montmorillonite was dispersed in anhydrous ethanol at a mass ratio of 50:1, and polyethylene glycol in an amount of 20% of the mass of the sodium-montmorillonite was added to react and dried.
[0053] Preparation of triblock copolymer-organic montmorillonite (the mass ratio of triblock copolymer to organic montmorillonite is 8:1):
[0054] a) dispersing the organic montmorillonite in water to obtain a suspension having a solid content of 22%;
[0055] b) adding the suspension to the triblock copolymer latex and uniformly mixing, wherein the mass ratio of the suspension to the triblock copolymer is 8:1, washing, and drying to obtain a hybrid material;
[0056] c) demulsifying the remaining triblock copolymer latex with calcium chloride, the mass of the calcium chloride being 0.5% of the triblock copolymer latex, and drying to obtain a copolymer;
[0057] d) The copolymer and the mixed material were mixed at a mass ratio of 10:1 on a two-roll mill at room temperature for 40 minutes.
[0058] Preparation of molded foaming composition:
[0059] Component A: 80 parts of polyether triol, 20 parts of high resilience polymer polyol H45, 0.8 parts of diethanolamine, 0.5 parts of silicone oil 6080, 0.3 parts of triethylenediamine 33% solution, 0.6 parts of dimethylethanolamine, 0.5 parts of triblock copolymer-organic montmorillonite, 1.2 parts of black paste 6025 and 3.2 parts of water;
[0060] Component B: 20 parts of methyl diisocyanate and 20 parts of polymethylene polyphenyl polyisocyanate;
[0061] S1. Stir the A combination at a speed of 100 r / min for 5 min;
[0062] S2, stirring the B combination at a speed of 15r / min for 2min;
[0063] S3. Mix the A component and the B component in a mass ratio of 5:2, stir at a speed of 20 r / min for 5 seconds, and then pour into a mold for reaction at a reaction temperature of 50°C.
[0064] Example 2
[0065] A foaming process for a molded foaming composition comprises the following steps:
[0066] Preparation of organic montmorillonite:
[0067] The dried sodium-nano montmorillonite was dispersed in anhydrous ethanol at a mass ratio of 50:1, and polyethylene glycol in an amount of 20% of the mass of the sodium-montmorillonite was added to react and dried.
[0068] Preparation of triblock copolymer-organic montmorillonite (the mass ratio of triblock copolymer to organic montmorillonite is 8:1):
[0069] a) dispersing the organic montmorillonite in water to obtain a suspension having a solid content of 20%;
[0070] b) adding the suspension to the triblock copolymer latex and uniformly mixing, wherein the mass ratio of the suspension to the triblock copolymer is 8:1, washing, and drying to obtain a hybrid material;
[0071] c) demulsifying the remaining triblock copolymer latex with calcium chloride, the mass of the calcium chloride being 0.1% of the triblock copolymer latex, and drying to obtain a copolymer;
[0072] d) The copolymer and the mixed material were mixed at a mass ratio of 10:1 on a two-roll mill at room temperature for 40 minutes.
[0073] Preparation of molded foaming composition:
[0074] Component A: 75 parts of polyether triol, 30 parts of high resilience polymer polyol H45, 0.5 parts of diethanolamine, 1 part of silicone oil 6080, 0.1 parts of triethylenediamine 33% solution, 0.2 parts of dimethylethanolamine, 0.1 parts of triblock copolymer-organic montmorillonite, 1 part of black paste 6025 and 2 parts of water;
[0075] Component B: 20 parts of methyl diisocyanate and 20 parts of polymethylene polyphenyl polyisocyanate;
[0076] S1. Stir the A combination at 50r / min for 5min;
[0077] S2, stirring the B combination at a speed of 15r / min for 2min;
[0078] S3. Mix the A component material and the B component material in a mass ratio of 5:1.8, stir at a speed of 15 r / min for 5 seconds, and then pour into a mold for reaction at a reaction temperature of 30°C.
[0079] Example 3
[0080] A foaming process for a molded foaming composition comprises the following steps:
[0081] Preparation of organic montmorillonite:
[0082] The dried sodium-nano montmorillonite was dispersed in anhydrous ethanol at a mass ratio of 50:1, and polyethylene glycol in an amount of 20% of the mass of the sodium-montmorillonite was added to react and dried.
[0083] Preparation of triblock copolymer-organic montmorillonite (the mass ratio of triblock copolymer to organic montmorillonite is 8:1):
[0084] a) dispersing the organic montmorillonite in water to obtain a suspension having a solid content of 25%;
[0085] b) adding the suspension to the triblock copolymer latex and uniformly mixing, wherein the mass ratio of the suspension to the triblock copolymer is 8:1, washing, and drying to obtain a hybrid material;
[0086] c) demulsifying the remaining triblock copolymer latex with calcium chloride, the mass of the calcium chloride being 1% of the triblock copolymer latex, and drying to obtain a copolymer;
[0087] d) The copolymer and the mixed material were mixed at a mass ratio of 10:1 on a two-roll mill at room temperature for 40 minutes.
[0088] Preparation of molded foaming composition:
[0089] Component A: 85 parts of polyether triol, 15 parts of high resilience polymer polyol H45, 1.5 parts of diethanolamine, 3 parts of silicone oil 6080, 0.5 parts of triethylenediamine 33% solution, 0.8 parts of dimethylethanolamine, 1 part of triblock copolymer-organic montmorillonite, 1.5 parts of black paste 6025 and 6 parts of water;
[0090] Component B: 20 parts of methyl diisocyanate and 20 parts of polymethylene polyphenyl polyisocyanate;
[0091] S1. Stir the A combination at a speed of 100 r / min for 5 min;
[0092] S2, stirring the B combination at a speed of 20r / min for 2min;
[0093] S3. Mix the A component material and the B component material in a mass ratio of 5:2.2, stir at a speed of 20 r / min for 5 seconds, and then pour into a mold for reaction at a reaction temperature of 65°C.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 1 is that polyethylene glycol is not used to modify the montmorillonite.
[0096] Comparative Example 2
[0097] The difference between this comparative example and Example 1 is that the triblock copolymer is not used to modify the organic montmorillonite.
[0098] Comparative Example 3
[0099] The difference between this comparative example and Example 1 is that the montmorillonite is micron montmorillonite.
[0100] Test example
[0101] The performance of the molded foaming composition of the embodiment and the comparative example was tested, and the physical properties were tested after aging for 24 hours, and the skin aging time was recorded (the room temperature was controlled at 20-25°C, and after exhaling, kraft paper was pasted on the surface of the foam to test the stickiness of the skin. The timing end point was when the foam was completely dry and no longer sticky to the paper, and the skin aging time was recorded). The density was tested using ISO 845-2006, the tensile strength and elongation at break were tested using ISO 1798-2008, the tear strength was tested using ISO 8067-2018, and the indentation hardness and resilience were tested according to QB / T 2080-2010. The results are as follows:
[0102] Table 1
[0103] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Density, KG / m 3 > 50 48 49 45 46 48 Indentation hardness (25%), N 96 94 92 80 75 84 Indentation hardness (65%), N 155 148 150 135 130 138 Tensile strength, KPa 189 182 180 155 140 162 Elongation at break, % 188 188 185 143 136 148 Tear strength, N / m 319 315 312 305 295 310 Resilience, % 69 65 68 55 50 62 Ripening time, min 4 5 4 5 4 6
[0104] According to Table 1, compared with the comparative example, the molded foam composition of the embodiment has better depression hardness, tensile strength, elongation at break, tear strength and resilience. In addition, the molding composition of the present invention matures faster, avoiding the need for additional heat during mass production and reducing energy consumption.
[0105] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A molded foaming composition, characterized in that: The invention comprises component A and component B. Component A comprises, by weight, 75-85 parts of polyether polyol, 15-30 parts of polymer polyol, 0.5-1.5 parts of diethanolamine, 1-3 parts of silicone oil, 0.1-0.5 parts of triethylenediamine, 0.2-0.8 parts of dimethylethanolamine, 0.1-1 parts of triblock copolymer-organic montmorillonite and 2-6 parts of water. Component B is isocyanate.
2. The molded foam composition according to claim 1, characterized in that: The triblock copolymer is poly-4-vinylpyridine-polystyrene-poly-4-vinylpyridine, and the organic montmorillonite is polyethylene glycol-modified montmorillonite.
3. The molded foam composition according to claim 2, characterized in that: The preparation method of the triblock copolymer-organic montmorillonite is as follows: a) dispersing the organic montmorillonite in water to obtain a suspension with a solid content of 20-25%; b) adding the suspension to the triblock copolymer latex, mixing uniformly, washing, and drying to obtain a mixed material; c) demulsifying the triblock copolymer latex with calcium chloride, drying, and obtaining a copolymer; d) mixing the copolymer and the mixed material at a mass ratio of 10:
1.
4. The molded foam composition according to claim 3, characterized in that: The preparation method of the organic montmorillonite is as follows: dispersing sodium-montmorillonite in anhydrous ethanol at a mass ratio of 50:1, adding polyethylene glycol in an amount of 20% of the mass of the sodium-montmorillonite for reaction, and drying.
5. The molded foam composition according to any one of claims 1 to 4, characterized in that: The mass ratio of component A to component B is 5:1.8-2.
2.
6. The molded foam composition according to claim 5, characterized in that: The polyether polyol is a polyether triol with a molecular weight of 4500-6500, a hydroxyl value of 26-35KOH / g, and a primary hydroxyl group of 60%-90%; the polymer polyol is a high-resilience polymer polyol H45; and the triethylene diamine is a triethylene diamine solution with a mass fraction of 33%.
7. The molded foam composition according to claim 6, characterized in that: The isocyanate comprises methyl diisocyanate and polymethylene polyphenyl polyisocyanate in a mass ratio of 1:
1.
8. The molded foam composition according to claim 7, characterized in that: The component A also includes 1-1.5 parts of a colorant by weight, and the colorant is black paste 6025.
9. A foaming process for a molded foam composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Stir the A combination at a speed of 50-100 r / min for 5 min; S2, stirring the B combination at a speed of 15-20r / min for 2min; S3, mixing the A component material and the B component material, stirring at a speed of 15-20 r / min for 5 seconds, and then pouring into a mold for reaction to obtain the molding foaming composition.
10. The foaming process of the molded foam composition according to claim 9, characterized in that: In step S3, the reaction temperature is 30-65°C.